Anaerobic Digestion Foaming Causes - Ganidi, Nafsika (Cranfield University, 2008)
Anaerobic digestion foaming has been encountered in several sewage treatment plants in the UK. Foaming has raised major concerns for the water utilities due to significant impacts on process efficiency and operational costs. Several foaming causes have been suggested over the past few years by researchers. However, the supporting experimental information is limited and in some cases site specific. The present report aimed to provide a better understanding of the anaerobic digestion foaming problem and to identify the underlying mechanisms of foaming. Field and laboratory investigation identified organic loading as a cause of foaming. Bench scale batch digestion studies in sludge showed that the critical organic loading for foaming was at 2.5 kg VS.m -3 while the 5 kg VS.m -3 resulted in persistent foaming. Moreover, full scale foaming digesters exhibited higher foaming potential in digested sludge under aeration in the laboratory than the full scale non- foaming digesters indicating that the concentration of surface active agents was higher. Further investigation of the effect of the surface active compounds, BSA and n-valeric acid on foaming showed that both compounds induced persistent foaming at all the examined concentrations. Filamentous bacteria contribution to foam initiation and stabilization was considered insignificant, apart from one occasion (FI:5), due to the abundance of filaments in foaming sludge (FI≤3) and their partitioning in foam (FI≤3). Part of the current work also assessed the cost implications of a foaming incident at the full scale. The antifoam cost was found to be of major concern for the water utilities costing between £1.30 and £13.00 per 1000 m 3 of digester volume per day. However, there was no information on biogas and energy loss whereas the information provided on cleaning, maintenance costs and manpower working hours was poor. Thus, the overall cost of a foaming incident at the full scale could not be estimated at this stage.